The level of students’ mastery of academic writing skills at the Department of Curricula and Methods of Teaching Arabic from the viewpoint of their faculty members - Al-Baladi, Azizah Awad Nakhilan; Haji, Khadijah Mohammed Omar (Journal of Educational and Psychological Sciences, 2021)
The current research aimed to explore the level of students’ mastery of academic writing skills at the Department of Curricula and Methods of Teaching Arabic from the viewpoint of their faculty members, and to find out if there are statistically significant differences between their views about the level of students’ mastery of these skills at the Department of Curricula and Methods of Teaching Arabic that are due to difference of universities. The author adopted the descriptive survey method, where she prepared a questionnaire composed of six basic skills containing forty-one sub-skills. The findings showed that the level of students’ mastery of academic writing skills at the Department of Curricula and Methods of Teaching Arabic is at the average and that there are no statistically significant differences between their views regarding the level of students’ mastery of those skills at the Department of Curricula and Methods of Teaching Arabic that are due to difference of universities. Based on these findings, the author made a set of recommendations the most prominent of which is that deanships of postgraduate studies at universities should issue academic writing accreditation standards for students' work and to make it a requisite to master at least 80% of academic writing skills. Also, there is the necessity to educate and enlighten students of the Department of Curricula and Methods of Teaching Arabic on the importance of academic writing and the acquisition of its skills.
Keywords: Writing; Academic writing; Academic writing skills; Students of the Department of Curricula and Methods of Teaching Arabic